Strategic directions of sustainable development of the tourism industry - L. Tranchenko; V. Yavorska; N. Tereshchuk (Journal of Education, Health and Sport, 2023)
Today, in the conditions of global restructuring and reorientation of economic sectors, the growth of people's needs and motives for tourism is important. Tourism as a branch of the economy is gradually taking leadership positions in many countries of the world, as well as in Ukraine in the future. Therefore, we have significant unrealized human, natural-resource, historical-cultural, tourist-recreational and scientific-technical potential, a good geographical location, and a favorable climate. Also, the peculiarity of the current situation in the country, economic and political instability, the conditions of the military conflict, insist on the further development of our state, which must necessarily include the creation of conditions for the development of the tourism industry.